Ferroelastic domain structure and phase transition in single-crystalline [PbZn1/3Nb2/3O3]1-x[PbTiO3]x observed via in situ x-ray microbeam. Issue 4 (April 2018) - Li, Tao; Du, Zehui; Tamura, Nobumichi; Ye, Mao; Inguva, Saikumar; Lu, Wei; Zeng, Xierong; Ke, Shanming; Huang, Haitao
Abstract: (1-x)Pb(Zn1/3 Nb2/3 )O3 -xPbTiO3 ((1-x)PZN-xPT in short) is one of the most important piezoelectric materials. In this work, we extensively investigated (1-x)PZN-xPT (x = 0.07–0.11) ferroelectric single crystals using in-situ synchrotron μXRD, complemented by TEM and PFM, to correlate microstructures with phase transitions. The results reveal that (i) at 25 °C, the equilibrium state of (1-x)PZN-xPT is a metastable orthorhombic phase for x = 0.07 and 0.08, while it shows coexistence of orthorhombic and tetragonal phases for x = 0.09 and x = 0.11, with all ferroelectric phases accompanied by ferroelastic domains; (ii) upon heating, the phase transformation in x = 0.07 is Orthorhombic → Monoclinic → Tetragonal → Cubic. The coexistence of ferroelectric tetragonal and paraelectric cubic phases was in-situ observed in x = 0.08 above Curie temperature ( T C ), and (iii) phase transition can be explained by the evolution of the ferroelectric and ferroelastic domains. These results disclose that (1-x)PZN-xPT are in an unstable regime, which is possible factor for its anomalous dielectric response and high piezoelectric coefficient.